Penerapan Sistem Hazard Analysis Critical Control Point (HACCP) pada Produk Asam–Asam Manyung di Kantin PT. Semen Indonesia (PERSERO) Tbk - Helvynda Dwita Yollanda (Universitas Airlangga, 2023)
Background: A food product that falls into the healthy category is a product that contains nutrients and substances that also do not contain harmful substances for human organs. Foods that can be included in the category are of good quality, if the food is suitable and safe to eat and consume. PT Semen Indonesia (Persero) Tbk provides facilities and infrastructure for canteens that already have cooperation with other parties, namely the party who takes care of catering, namely crown catering where the party facilitates the provision of food for employees in developing the performance of these employees. One of the products issued by the party is Manyung Asam. Objectives: This research was aimed to identify the application of HACCP System on Asam-Asam Manyung Product. Method: The method used in the implementation of the research is descriptive qualitative which includes the implementation of observations in the field which are carried out directly and also the implementation of interviews with crown catering employees who work in the canteen of PT Semen Indonesia (Persero), Tbk. Result: The stages in carrying out production begin through the stages of the process of receiving raw materials from manyung acid dishes to end with the presentation of the food. The implementation of the process of making manyung asam found that there are three stages which are crisis points (CCP) that should be watched out for, namely being in the stage of the frozen fish process that begins to be stored, then the liquid process of fish that has been frozen before and ends with the presentation of the food. Procedures for carrying out risk control that can be carried out during the process of storing frozen fish are carried out regular checks in order to find out the temperature used whether it is in accordance with applicable standards. The liquid stages of frozen fish utilize one of the many uses of techniques from the four mandatory thawing techniques to be carried out so as not to become a source of development of various microorganisms and the stages of presentation that are required to pay attention to the status of the food product so that in conditions of being stuck in a fence can carry out prevention of external contamination. Conclusion: The results of this study can be useful as input and improvement of food quality and can be applied to the HACCP system in other food products. So that the food products produced are safe for consumption.